The Impact of COVID-19 on women - United Nations (United Nations Entity for Gender Equality and the Empowerment of Women (UN Women); United Nations Secretariat, 2020)
The year 2020, marking the twenty-fifth anniversary of the Beijing Platform for Action, was intended to be ground-breaking for gender equality. Instead, with the spread of the COVID-19 pandemic, even the limited gains made in the past decades are at risk of being rolled back. The pandemic is deepening pre-existing inequalities, exposing vulnerabilities in social, political and economic systems which are in turn amplifying the impacts of the pandemic. Across every sphere, from health to the economy, security to social protection, the impacts of COVID-19 are exacerbated for women and girls simply by virtue of their sex. This policy brief by the UN Secretary-General explores how women and girls’ lives are changing in the face of COVID-19, and outlines suggested priority measures to accompany both the immediate response and longer-term recovery efforts.
Keywords: 2000 à aujourd'hui; 2020-2029; covid-19; discipline; droit; droits des femmes*; droits humains; pandémie; projet charge mentale; périodes historiques; santé; science politique et droit; thématiques; violences; violences sexistes et sexuelles